Signs of illness in Kenyan infants aged less than 60 days - English Mike; Ngama Mwanajuma; Mwalekwa Laura; Peshu Norbert (Bulletin of the World Health Organization, 2004)
OBJECTIVE: Little data has been published on the presenting symptoms and signs among ill infants aged <60 days from developing countries. We aimed to describe and evaluate the potential of simple clinical features to identify severe illness among young infants who present to rural district hospitals in Kenya. METHODS: Standardized assessment tools were designed to record clinical symptoms and signs. Data were collected prospectively on all infants aged <60 days who weighed >1.5 kg and were admitted over an 18-month period. The same data were collected prospectively from infants recruited to a contemporaneous hospital birth cohort who became ill and were assessed and treated as outpatients at the same hospital. FINDINGS: Data on 467 outpatient consultations and 769 inpatient episodes were available for analysis. These data highlighted the importance of findings in the history, particularly breathing difficulties, abnormal feeding, and abnormal behaviour, as well as clinical signs in the evaluation of young infants. They indicated possible important differences in the panel of signs useful for detecting severe illness in infants aged 0-6 days and those aged 7-59 days. They also showed that some simplification of current guidelines that still preserved the sensitivity and specificity for detecting very severe disease might be possible. CONCLUSION: Simple clinical features may allow distinction between severe and non-severe illness to be made with reasonable confidence. Prospective studies on an adequate scale are needed urgently to provide current integrated management of childhood illness guidelines for young infants with an adequate evidence base.